If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 4 + 8u + 2t = 0 Reorder the terms: 4 + 2t + 2t + 8u = 0 Combine like terms: 2t + 2t = 4t 4 + 4t + 8u = 0 Solving 4 + 4t + 8u = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 4t + -4 + 8u = 0 + -4 Reorder the terms: 4 + -4 + 4t + 8u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 4t + 8u = 0 + -4 4t + 8u = 0 + -4 Combine like terms: 0 + -4 = -4 4t + 8u = -4 Add '-8u' to each side of the equation. 4t + 8u + -8u = -4 + -8u Combine like terms: 8u + -8u = 0 4t + 0 = -4 + -8u 4t = -4 + -8u Divide each side by '4'. t = -1 + -2u Simplifying t = -1 + -2u
| H(t)=-16t^2+64t+ho | | k^2+100=20k | | 6=2x+2.5y | | 6t+4u+1+9u= | | 273+286+n=943 | | 4x^2-4x+7=6 | | 6x^2+43x-15= | | 7+u+9t+5u= | | 2sinx+3cosx=4x | | 9h=7h | | 6x+10=64-3x | | 0=4x^3-12x^2-24x+32 | | .04x^2-4x=0 | | 2[5+2(9-4)]= | | 12+8x=4x+20 | | 9u+4+8t+3u= | | 5-2x+2=15 | | 2y=6-2.5x | | 9xsquared+16x=41 | | 9x+2=-5 | | 3x^2-12x-5=-6x^2 | | 6=2y+2.5x | | 6=2.5x+2y | | -9x+2=5 | | 5=3x-2+4x+1 | | 8x-(22x+7)=5x(2x-2)+8 | | 7x+5y-5(4x-7y)= | | B=(r+k)f | | y=15-10 | | 9y-8y-3=7 | | -81=5x-2(-2x+9) | | 3p^5=12 |